Testosterone replacement therapy improves health‐related quality of life for patients with late‐onset hypogonadism: a meta‐analysis of randomized controlled trials. (8th July 2016) - Nian, Y.; Ding, M.; Hu, S.; He, H.; Cheng, S.; Yi, L.; Li, Y.; Wang, Y.
Summary: Although testosterone replacement therapy can restore serum testosterone concentrations to normal level in late‐onset hypogonadism patients, whether it can improve patients' quality of life remains uncertain. Therefore, we perform a meta‐analysis of randomized controlled trials on this issue. Five randomized controlled trials total 1, 212 patients were included. Fixed‐effect model was used to calculate the weighted mean difference of score of Aging Males' Symptom rating scale. Our result reveals that testosterone replacement therapy improves patients' health‐related quality of life in terms of the decrease in the AMS total score [WMD = −2.96 (−4.21, −1.71), p  < .00001] and the psychological [WMD = −0.89 (−1.41, −0.37), p  = .0008], somatic [WMD = −0.89 (−1.41, −0.37), p  = .0008] and sexual [WMD = −1.29 (−1.75, −0.83), p  < .00001] subscale score.